Experience in the Treatment of Hemangioma in Children - Valentina V. Perlovskaya; Viktor N. Stalmakhovich; Irina N. Kaygorodova; Galina I. Stalmakhovich (Acta Biomedica Scientifica, 2019)
The article reflects modern views on epidemiology, clinical manifestations, classification, principles of diagnostics and treatment of hemangiomas. The purpose of our study was the analysis of the results of different methods of treatment inof children with hemangioma over a ten-year period (from 2007 to 2017) at Irkutsk Regional Children Hospital. We have found a significant reduction in cases of invasive treatment in patients with this pathology. In 2017, inhemangioma was excised in 179 children, and in 2017, this method was used only in 28 patients. Since 2009 cryolysis of vascular neoplasms has not been performedcryolysis. Conservative treatment of hemangiomas include hormone therapy with prednisone as well as systemic and local treatment with beta-adrenergic blocking agents. At the same time, we showed that conservative treatment of hemangiomas is effective before surgery. That is confirmed by the clinical observation of the child with an extensive perineal hemangioma, who underwent the combined treatment using surgical cryodestruction and hormone therapy. This example shows that a good aesthetic result has been obtained only when using hormone therapy, while partial excision of hemangiomas resulted in a violation of the anatomy of the external genitalia, and cryodestruction resulted in an extensive hypertrophic scar on both buttocks. It is concluded that the reasons for the change in treatment tactics in children with hemangiomas are determined by the possibility of using non-invasive methods with obtaining the optimal result of treatment in both oncological and aesthetic terms.